TANGGUNG JAWAB PEMERINTAH TERHADAP PELAYANAN KESEHATAN BAGI WARGA LANJUT USIA DALAM HUKUM POSITIF INDONESIA - Heryani, Ririn; Iriansyah; Ardiansyah (Collegium Studiosum Journal, 2023)
During the pandemic and work-from-home policies, it is feared that elderly people live together with all generations in limited space, it is feared that this will increase elderly depression. On the other hand, a number of elderly people are lonely, because their children cannot see or visit their parents regularly due to social restrictions. In fact, when it is normal, the condition of the elderly still requires attention in various ways. The purpose of this research is to analyze the Government's Responsibility for Health Services for the Elderly in Indonesian Positive Law and to analyze the ideal of the Government's Responsibility for Health Services for the Elderly. The method used is normative legal research. Based on the research results, it is known that the Government's Responsibility for Health Services for the Elderly in Indonesian Positive Law is that the Indonesian Government has the responsibility to provide good and fair health services for all its citizens, including the elderly. This responsibility is reflected in several laws and regulations governing health in Indonesia. Health Law This law establishes the basic principles for administering the health system in Indonesia, including health services for elderly citizens.